Mobile Compression Reduces Bleeding-related Readmissions and Wound Complications After THA and TKA - Arsoy, Diren (Clin Orthop Relat Res, 2018)
BACKGROUND: The use of chemoprophylaxis to prevent thromboembolic disease after primary THA and TKA can be associated with postoperative bleeding complications. Mechanical prophylaxis has been studied as an alternative to chemoprophylaxis with greater safety in patients undergoing THA, but no data have been published comparing the safety of chemoprophylaxis versus mechanical methods for patients undergoing TKA. The risk of readmission resulting from bleeding and venous thromboembolism (VTE) has also not been determined for patients undergoing THA or TKA when treated with low-molecular-weight heparin (LMWH) alone compared with mechanical prophylaxis plus aspirin (ASA). QUESTION/PURPOSES: We sought to answer four questions: For the THA and TKA cohorts, respectively, (1) was the incidence of readmission resulting from VTE and bleeding complications higher with LMWH than mobile compression plus ASA; and (2) was the incidence of wound bleeding complications higher with LMWH than mechanical compression plus ASA? For the TKA cohort specifically, (3) was the frequency of systemic bleeding events and complications related to chemical prophylaxis higher with LMWH compared with mechanical compression plus ASA? (4) Was there a difference in symptomatic VTEs between LMWH and mechanical compression plus ASA? METHODS: Between November 2008 and April 2011, 632 patients underwent primary THA and TKA. Seventy-two patients (11%) were identified before surgery as being at high risk for VTE (31 patients) or bleeding (41 patients) and were excluded from the study. Five hundred sixty patients (89%) were considered to be at standard risk for VTE and bleeding and comprise the study cohort. Between November 2008 and November 2009, 252 patients (76 THAs, 176 TKAs) underwent THA and TKA and were treated with LMWH (5 mg dalteparin given subcutaneously daily for 14 days) and in-hospital nonmobile mechanical compression. Between November 2009 and April 2011, a total of 308 patients undergoing THA and TKA (108 THAs, 200 TKAs) were treated using a mobile compression device plus oral aspirin once daily for 2 weeks after surgery. All complications and readmissions that occurred within 6 weeks of surgery were noted. There were no differences between the VTE treatment groups with regard to age, sex, or body mass index. RESULTS: For the THA cohort, there was no difference in the frequency of readmission for a bleeding complication (wound or systemic) between the two groups (2.6% for LMWH versus 0.9% for mobile compression; p = 0.57; odds ratio [OR], 2.9). Patients undergoing TKA treated with LMWH had higher readmission rates within 6 weeks of surgery because of a bleeding complication, a wound infection, or the development of a VTE (6.8% for LMWH versus 1.5% for mobile compression; p = 0.015; OR, 4.8). For the THA cohort, there was higher wound bleeding complication frequency with LMWH (9.2% for LMWH versus 0.9% for mechanical compression; p = 0.009; OR, 10.9). Patients undergoing TKA treated with LMWH had a higher frequency of wound bleeding complications or infection (3.9% for LMWH versus 0.5% for mobile compression; p = 0.028; OR, 8.2). Patients undergoing TKA treated with LMWH had higher rates of systemic bleeding or a complication secondary to LMWH administration (2.8% for LMWH versus 0% for mobile compression; p = 0.022; OR, 12.8). No difference was noted in the rate of symptomatic VTEs between either group (for THA: 2.6% for the LMWH group versus 1.9% for the mechanical compression group; p = 1; for TKA: 1.1% versus 0%, respectively; p = 0.22). CONCLUSIONS: Based on these results, we advocate for routine use of mobile mechanical compression devices in the prevention of VTEs and complications associated with more potent chemical anticoagulants. However, more focused randomized clinical trials are needed to validate these findings. LEVEL OF EVIDENCE: Level III, therapeutic study.